2021
DOI: 10.33920/sel-05-2112-01
|View full text |Cite
|
Sign up to set email alerts
|

Features of the formation of the bacterial community of the rumen and the biochemical status of the cows depending on the protein source

Abstract: The results of scientific and economic experiment on the use of protein concentrate “AgroMatic” in feeding highly productive cows of Ayrshire breed during lactation have been provided in the article. The use of protein concentrate “Agro-Matic” in the rations of dairy cattle in the amount of 1,0 and 1,5 kg/head/day has been leaded to an increase in the content of cellulolytic microflora at the end of lactation compared with the control group. At the same time, the level of microorganisms that stimulate and prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Analysis of the rumen content showed that the number of Bacteroidetes in cows of groups (1.0 and 1.5 kg/day) receiving protein concentrate in their diets was reduced by 1.5% and 2.9%. There were no significant differences between the control group and the groups receiving PCAM supplements and in most of the rumen microbiota, with the exception of pathogenic microorganisms such as Peptococcus and Fusobacteria; a significant decrease was noted between the control group and the groups receiving PCAM supplements [31,34,35].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Analysis of the rumen content showed that the number of Bacteroidetes in cows of groups (1.0 and 1.5 kg/day) receiving protein concentrate in their diets was reduced by 1.5% and 2.9%. There were no significant differences between the control group and the groups receiving PCAM supplements and in most of the rumen microbiota, with the exception of pathogenic microorganisms such as Peptococcus and Fusobacteria; a significant decrease was noted between the control group and the groups receiving PCAM supplements [31,34,35].…”
Section: Introductionmentioning
confidence: 77%
“…In our early works devoted to the use of a new protein feed protein concentrate Agro-Matic (PCAM), which is made from poultry meat processing waste and crushed white lupine grain in feeding lactating cows [31][32][33][34][35], it was shown that the inclusion of it in various quantities in the diet of highly productive Ayrshire dairy cows showed a positive effect on milk productivity and milk quality throughout the lactation period, improved digestibility of nutrients, nitrogen retention in the body without deterioration of the physiological and the sanitary condition of cows. Moreover, the inclusion of 1.5 kg/head/day PCAM was the best regarding economic benefits [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%